The chemotherapy-induced peripheral neuropathy outcome measures standardization study: from consensus to the first validity and reliability findings - Cavaletti, G.; Cornblath, D.R.; Merkies, I.S.J.; Postma, T.J.; Rossi, E.; Frigeni, B.; Alberti, P.; Bruna, J.; Velasco, R.; Argyriou, A.A.; Kalofonos, H.P.; Psimaras, D.; et al. (Annals of oncology, 2013)
Chemotherapy-induced peripheral neuropathy (CIPN) is a debilitating and dose-limiting complication of cancer treatment. Thus far, the impact of CIPN has not been studied in a systematic clinimetric manner. The objective of the study was to select outcome measures for CIPN evaluation and to establish their validity and reproducibility in a cross-sectional multicenter study. After literature review and a consensus meeting among experts, face/content validity were obtained for the following selected scales: the National Cancer Institute-Common Toxicity Criteria (NCI-CTC), the Total Neuropathy Score clinical version (TNSc), the modified Inflammatory Neuropathy Cause and Treatment (INCAT) group sensory sumscore (mISS), the European Organization for Research and Treatment of Cancer (EORTC) QLQ-C30, and CIPN20 quality-of-life measures. A total of 281 patients with stable CIPN were examined. Validity (correlation) and reliability studies were carried out. Good inter-/intra-observer scores were obtained for the TNSc, mISS, and NCI-CTC sensory/motor subscales. Test–retest values were also good for the EORTC QLQ-C30 and CIPN20. Acceptable validity scores were obtained through the correlation among the measures. Good validity and reliability scores were demonstrated for the set of selected impairment and quality-of-life outcome measures in CIPN. Future studies are planned to investigate the responsiveness aspects of these measures.